Equity Implications of the Universal Primary Education Funding Mechanisms in Uganda - Muhammad, Kiggundu Musoke; Itaaga, Nicholas (Review of Knowledge Economy, 2015)
The study sought to establish whether or not the way Universal Primary Education (UPE) is funded in Uganda is equitable among the different socioeconomic groups, gender, religions and disability. This was based on the view that if the expenditure on education is to benefit the entire society, it must be equitably distributed. Furthermore, specific groups have special requirements that need specific attention. The study adopted a cross-sectional survey design and was majorly qualitative. Key stakeholders interviewed included officials at the Ministry of Education and Sports headquarters, District Education Officials, head teachers, teachers, parents, pupils, and opinion leaders in ten (10) districts in Uganda. The study findings revealed that although some elements of equity were evident, there were no deliberate efforts by the financiers of the UPE program to ensure equity. The study also revealed measures like increased funding, sensitization of key stakeholders, linkages between sectors and needs assessment for appropriate intervention in order to ensure equity in funding. The study recommended that the Government of Uganda and other stakeholders must put in place deliberate provisions to ensure equitable funding of the UPE program. NB: The national currency in Uganda is the Uganda Shilling (Shs.) and the exchange rate at the time of conducting the study was 1US = 2,650 Shs.